Determinants of Firm Value in Food and Beverage Industry - Zahri Ulfiah; Fanny Suzuda Pohan (Greenation International Journal of Economics and Accounting, 2024)
This study aims to examine the effect of debt policy, dividend policy and profitability on firm value in food and beverage companies listed on the Indonesia stock exchange for the 2019-2023 period. This type of research is associative. The population of this research is 95 companies. The sample was determined by purposive sampling technique as many as 17 companies. The type of data in this study is secondary data with quantitative research methods and descriptive approaches. Data analysis used is panel data regression analysis. This research is processed using software EViews 12. The results of this study indicate that debt policy proxied by Debt-to-Equity Ratio (DER) and profitability proxied by return on assets (ROA) have a significant effect on firm value, while dividend policy proxied by Dividend Payout Ratio (DPR) has no effect on firm value. Simultaneously, debt policy, dividend policy and profitability have an effect on firm value.